Internet connectivity disruption in Venezuela (Venezuela) - Voidly (2026)
CRITICAL severity disruption detected in Venezuela. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: VE-2026-0265
Keywords: internet disruption; VE; disruption; critical